Coping with commodification : hybrid strategies in Asian law firms - Chow, Dawn Y. (2021)
Research has indicated that many organizations are located at complex boundary zones which are guided by differing institutional logics. As varied institutional logics overlap, there may be strains on organizations which are trapped within shared boundaries. To reduce such strains and to respond to institutional logic clash, organizations within different fields tend to resort to hybrid strategies of action. However, despite the plethora of studies, there is still a lack of a coherent body of research that addresses the question of how and why organizations experience institutional complexity differently. In response to calls for research on how particular organizational attributes of firms would matter to the experience of firms in situ, we examine how a particular organizational attribute – organizational size— matters, by conducting comparative research on a large versus small Singapore law firm. We thus contribute to the research by showing how hybrid strategies enable organizations to resolve institutional logic clash. Also, we reveal the structural condition underlying the firms’ hybrid strategies in response to commodification pressures. Contrary to extant research that suggests otherwise, our findings demonstrate that small, rather than large firms, are in fact better suited to adapt to institutional change, so long as they can carve out a particular niche market for themselves. Additionally, unlike extant research in international business that may have hypothesized a rather large impact of MNCs on a country’s competitive landscape, we find that there are limits to the influence that an MNC has, especially on smaller local players.